The policy of inclusive education and the future of specialized institutions in Brazil - Encéia Gonçalves Mendes (Arizona State University, 2019)
The present article is a theoretical essay that compiles a historical analysis of the special education policy in Brazil, focusing on the changes produced from the year 2000 with a view to radicalize the perspective of school inclusion. Since then, this field has been subject to strong tensions between those who point to the need to educate all the students of the target public of special education in the common schools, and others who recommend a more cautious approach, based on empirical analysis and historical considerations. At the heart of this debate is the decision of what to do with the traditional specialized institutions of the sector, and in this sense the proposals go from extinction to prevent segregation, they also recommend their reconfiguration as a service to support inclusive schooling, a predominant tendency in the current policy, to those who defend its maintenance. In the present work, we analyzed such possibilities, taking into account historical, legal, political, pragmatic and scientific arguments, in order to conclude that they must be reconfigured, not as centers of support, but as special schools, in a diversified network of articulated services to support the needs of certain students of the target public of special education.